2010
DOI: 10.1073/pnas.1005938107
|View full text |Cite
|
Sign up to set email alerts
|

Human ESCRT-III and VPS4 proteins are required for centrosome and spindle maintenance

Abstract: The ESCRT pathway helps mediate the final abscission step of cytokinesis in mammals and archaea. In mammals, two early acting proteins of the ESCRT pathway, ALIX and TSG101, are recruited to the midbody through direct interactions with the phosphoprotein CEP55. CEP55 resides at the centrosome through most of the cell cycle but then migrates to the midbody at the start of cytokinesis, suggesting that the ESCRT pathway may also have centrosomal links. Here, we have systematically analyzed the requirements for la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
208
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(221 citation statements)
references
References 41 publications
9
208
1
1
Order By: Relevance
“…Now evidence has been presented that an ESCRT-III complex containing CHMP7 as a subunit is involved in resealing of the nuclear envelope during mitosis (Olmos et al 2015;Vietri et al 2015). Earlier work also pointed to a role of CHMP7 in mitosis (Morita et al 2010). In another report, it was suggested that a novel ESCRT-III-like complex could be involved in the surveillance of nuclear pore complex (NPC) assembly at the nuclear membrane in yeast (Webster et al 2014), but it is not clear whether this complex contains a CHMP7 ortholog.…”
mentioning
confidence: 98%
“…Now evidence has been presented that an ESCRT-III complex containing CHMP7 as a subunit is involved in resealing of the nuclear envelope during mitosis (Olmos et al 2015;Vietri et al 2015). Earlier work also pointed to a role of CHMP7 in mitosis (Morita et al 2010). In another report, it was suggested that a novel ESCRT-III-like complex could be involved in the surveillance of nuclear pore complex (NPC) assembly at the nuclear membrane in yeast (Webster et al 2014), but it is not clear whether this complex contains a CHMP7 ortholog.…”
mentioning
confidence: 98%
“…In addition, ESCRTs are known to mediate fission of small vesicles (<50 nm diameter) or viruses (<100 nm) (7), making it unclear how they could mediate largescale scission of membranes >1 ÎŒm in diameter (3,5), as exist within the intercellular bridge during cytokinetic abscission. Finally, cytokinetic failure in the absence of ESCRTs could be an indirect effect of ESCRTs' having multiple functions in cell division, including roles in maintaining the integrity of centrosomes (18) and the midbody (13).…”
mentioning
confidence: 99%
“…Cells lacking the ESCRT-III and VPS4 proteins displayed abnormalities in abscission, and unexpectedly, at earlier mitotic stages, with centrosome number, morphology and function being altered (Morita, et al, 2010). Given that human CC2D1A interacts with CHMP4B and CHMP4C, and that CC2D1A-targeted siRNA results in multipolar spindles, it is noteworthy that this same phenotype is evident in cells treated with siRNA to ESCRT-III/VPS4 proteins, specifically, CHMP1A, CHMP1B, CHMP2B, CHMP4B, CHMP4C, CHMP7, VPS4A, and VPS4B (Morita, et al, 2010). These cells additionally had greater numbers of centrosomes and spindles.…”
Section: Cc2d1a and Centrosomal Functionmentioning
confidence: 99%
“…ESCRT-III and VPS4 proteins are localized to the centrosomes, regulating both maintenance or proliferation and cell division at the midbodies during abscission (Carlton, et al, 2008;Lindas, et al, 2008;Morita, et al, 2007;Samson, et al, 2008). Cells lacking the ESCRT-III and VPS4 proteins displayed abnormalities in abscission, and unexpectedly, at earlier mitotic stages, with centrosome number, morphology and function being altered (Morita, et al, 2010). Given that human CC2D1A interacts with CHMP4B and CHMP4C, and that CC2D1A-targeted siRNA results in multipolar spindles, it is noteworthy that this same phenotype is evident in cells treated with siRNA to ESCRT-III/VPS4 proteins, specifically, CHMP1A, CHMP1B, CHMP2B, CHMP4B, CHMP4C, CHMP7, VPS4A, and VPS4B (Morita, et al, 2010).…”
Section: Cc2d1a and Centrosomal Functionmentioning
confidence: 99%